2017
DOI: 10.1038/ni.3659
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial macrophage-derived IL-1β stimulates insulin, and both synergistically promote glucose disposal and inflammation

Abstract: The deleterious effect of chronic activation of the IL-1 system on type 2 diabetes and other metabolic diseases is well documented. However, a possible physiological role for IL-1 in glucose metabolism has remained unexplored. Here we found that feeding induced a physiological increase in the number of peritoneal macrophages that secreted IL-1, in a glucose-dependent manner. Subsequently, IL-1 contributed to the postprandial stimulation of insulin secretion. Accordingly, lack of endogenous IL-1 signaling in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
258
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(290 citation statements)
references
References 62 publications
25
258
1
6
Order By: Relevance
“…Moreover, the synergistic contribution of insulin and proinflammatory cytokines to the stimulation of the immune system has been reported. Dror et al (34) found that insulin stimulates IL-1b secretion by resident macrophages, which could explain the mechanisms by which insulin restored IL-1β levels in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the synergistic contribution of insulin and proinflammatory cytokines to the stimulation of the immune system has been reported. Dror et al (34) found that insulin stimulates IL-1b secretion by resident macrophages, which could explain the mechanisms by which insulin restored IL-1β levels in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Whether this is relevant to the metabolic improvements observed after surgery is unclear, yet it indicates that the immune environment is significantly altered with VSG which fits with the potent upregulation of T cells present in the eWAT. Recently, there has also been evidence that some cytokines can act directly on systemic metabolic changes via immune cells, such as IL-1β being produced by peritoneal macrophages in response to feeding and subsequently acting on the pancreatic β cells to increase insulin secretion [36]. In the light of this, there is even more reason to believe that changes in the immune cells/cytokines after surgery could be relevant to metabolic improvements after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, has several limitations such as the small sample sizes and the fact that dietary intake and blood collection time was not standardized. Not only hormone but also cytokine concentrations, for instance, IL-1β are known to change post-prandially (20), yet this is almost never considered in TB biomarker studies available in the literature and should be taken into account in any future studies. Despite the limitations, typical treatment responses were observed when looking at the changes in hormone concentrations during TB treatment and it would appear that cortisol, DHEA, T4, and amylin (total) are the major role players in the host response to M.tb and are potential marker candidates to differentiate treatment outcome.…”
Section: Discussionmentioning
confidence: 99%